Gods of the North - Coats, Lucy (Coats, Lucy. Beasts of Olympus, 2017)
"Odin, the ruler of the Asgardians, has an important mission for Demon. Goldbristle, the gods' prized shining boar, is losing his light. Now Demon must travel to Asgard in the North to search this cold, snowy land for anything that might cure this beast." -back of cover.